Environmental influence and species occurrence of yellowjacket drones in an invaded area - Agustina P. Porrino; Maité Masciocchi; Andrés S. Martínez (Scientific Reports)
Abstract During the mating season, reproductive individuals of numerous insect species gather in rendezvous areas, which increases mating opportunities. Male hymenopterans often have to move considerable distances during a particular season, searching or waiting for receptive females. Such behavior is likely driven by a complex combination of individual and species-specific traits, environmental influence, and landscape cues. Our field study aimed to determine factors affecting the occurrence of Vespula spp. drones, focusing on the influence of vegetation traits, atmospheric factors and diel effects, and the species occurrence proportion in an invaded area in Patagonia. Our results indicate that the probability of drone presence over different types of vegetation is affected both by plant species and height. Also, weather and time of day influence the number of individuals simultaneously gathering, as higher abundances of flying drones are found in early hours, warmer days and at low cloud cover. Lastly, through mid-flight drone captures, we determined that both V. germanica and V. vulgaris drones are found concurrently in the same rendezvous areas. This constitutes the first exploratory field study reporting the heterospecific occurrence of Vespula spp. drones and overall, our results contribute to the understanding of yellowjackets mating systems.